2015
DOI: 10.4314/gjass.v13i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive effect of cabbage (<i>Brassica oleracea</i>) on growth, obesity, lipidaemia and haematology in broiler and pullet chickens

Abstract: Efficacy of cabbage (Brassica oleracea) for ameliorating the adverse metabolic syndrome side-effects of genetically improved growth rate in chickens was examined. Sixty-four (64) day-old birds (32 Marshall Broilers and 32 Harco Black Pullets) were randomly assigned to groups of eight genotype-matched birds in a 2-factor layout within a Completely Randomized Design (CRD). Within genotype, each group was randomly assigned one of four diets (basal/control diet containing 0% cabbage, and, basal diet supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Therefore, broccoli has an effective role in improving health, including body weight, and this is consistent with what was mentioned by [16]. and by the scientist [17]. which indicated that the use of broccoli by 30% leads to an increase in the weight of broiler chicken.The results showed that feeding on broccoli sprouted seed powder at a concentration of 15% and 30% led to an improvement in the weight gain rates of laboratory animals, which indicates the effect of this feeding in improving and raising the immunity of laboratory animals and reducing the effects of Sandmmun.…”
Section: Effect Of Broccoli Sprouted Seed Powder On Average Weights O...supporting
confidence: 87%
“…Therefore, broccoli has an effective role in improving health, including body weight, and this is consistent with what was mentioned by [16]. and by the scientist [17]. which indicated that the use of broccoli by 30% leads to an increase in the weight of broiler chicken.The results showed that feeding on broccoli sprouted seed powder at a concentration of 15% and 30% led to an improvement in the weight gain rates of laboratory animals, which indicates the effect of this feeding in improving and raising the immunity of laboratory animals and reducing the effects of Sandmmun.…”
Section: Effect Of Broccoli Sprouted Seed Powder On Average Weights O...supporting
confidence: 87%
“…The body mass index was significantly influenced by the inclusion of ELM and this was in agreement with the reports of Akintunde et al (2021b) who observed that the inclusion of Moringa oleifera seed meal significantly influenced BMI in Yoruba Ecotype chickens and Marshall broiler chickens. Similar observations in the BMIs of broiler and pullets chickens fed cabbage were also made by Adesina and Toye (2014). However, the values obtained for BMIs in the study at starter (0.39-0.43 g/cm 2 ) and finisher (0.50-0.58 g/cm 2 ) were in proximity to the ranges reported for pullets chickens at week 4 (0.31-0.36 g/cm 2 ) and week 7 (0.48-0.56 g/cm 2 ) reported by Oludoyi and Toye (2012) and the range of 0.47-0.61 g/cm 2 reported by Akintunde et al (2021b) for Yoruba Ecotype Chickens.…”
Section: Growth Pattern and Physiological Response Of Japanese Quails...supporting
confidence: 77%